Law Enforcement Against Human Trafficking In The Rentaru Kareshi Phenomenon - Dirkareshza, Nada Prima; Agustanti, Rosalia Dika (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Rentaru Kareshi is a term that refers to a "rental girlfriend" in Japan. This phenomenon has become a serious concern in recent years, due to its vulnerability to human trafficking, especially in cases of sexual exploitation. In addition, the buying and selling of rental services is carried out through intermediaries, namely platforms on social media that recruit these talents. This raises the question of whether this is a form of human trafficking. The aim of this research is to find out how the Ius Constitutum relates to the Rentaru Kareshi phenomenon in Indonesia and how law enforcement handles the occurrence of criminal acts in the Rentaru Kareshi Phenomenon. The method used is the Normative Juridical research method, with a problem approach, Legislative approach, Conceptual Approach, and comparative approach and the data collection technique used by the author is the literature study method. Even though the Ius Constitutum Indonesia has supported it, legal enforcement regarding this boyfriend rental service is still not visible because the phenomenon of boyfriend rental services can be said to be a new phenomenon causing a lack of understanding of law enforcement resulting in the absence of law enforcement actions.